\(\frac{5^2}{1.4}\)+ \(\frac{5^2}{4.7}\)+ ... + 
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 5 2017

\(A=\frac{2}{3}.\left(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{97}-\frac{1}{100}\right)\)

\(A=\frac{2}{3}.\left(1-\frac{1}{100}\right)\)

\(A=\frac{2}{3}.\frac{99}{100}\)

\(A=\frac{33}{50}\)

13 tháng 5 2017

33/50

1 tháng 8 2020

\(\left(2\right)K=\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+...+\frac{1}{9900}\)

\(K=\frac{1}{2\cdot3}+\frac{1}{3\cdot4}+\frac{1}{4\cdot5}+...+\frac{1}{99\cdot100}\)

\(K=\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{99}-\frac{1}{100}\)

\(K=\frac{1}{2}-\frac{1}{100}=\frac{49}{100}\)

\(\left(3\right)L=\frac{5}{1\cdot4}+\frac{5}{4\cdot7}+\frac{5}{7\cdot10}+...+\frac{5}{100\cdot103}\)

\(L=\frac{5}{3}\cdot\left(\frac{1}{1}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{10}+...+\frac{1}{100}-\frac{1}{103}\right)\)

\(L=\frac{5}{3}\cdot\left(\frac{1}{1}-\frac{1}{103}\right)=\frac{5}{3}\cdot\frac{102}{103}=\frac{510}{309}=\frac{170}{103}\)

1 tháng 8 2020

Trả lời:

2,\(K=\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+...+\frac{1}{9900}\)

\(K=\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+...+\frac{1}{99.100}\)

\(K=\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{99}-\frac{1}{100}\)

\(K=\frac{1}{2}-\frac{1}{100}\)

\(K=\frac{49}{100}\)

3,\(L=\frac{5}{1.4}+\frac{5}{4.7}+...+\frac{5}{100.103}\)

\(L=\frac{5}{3}\times\left(\frac{3}{1.4}+\frac{3}{4.7}+...+\frac{3}{100.103}\right)\)

\(L=\frac{5}{3}\times\left(\frac{1}{1}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{100}-\frac{1}{103}\right)\)

\(L=\frac{5}{3}\times\left(\frac{1}{1}-\frac{1}{103}\right)\)

\(L=\frac{5}{3}\times\frac{102}{103}\)

\(L=\frac{170}{103}\)

Học tốt 

27 tháng 4 2017

=\(\frac{5}{3}\cdot\left(\frac{3}{1\cdot4}+\frac{3}{4\cdot7}+...+\frac{3}{100\cdot103}\right)\)

=\(\frac{5}{3}\cdot\left(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{100}-\frac{1}{103}\right)\)

=\(\frac{5}{3}\cdot\left(1-\frac{1}{103}\right)\)

=\(\frac{5}{3}\cdot\frac{102}{103}\)=\(\frac{170}{103}\)

Vậy D=\(\frac{170}{103}\)

22 tháng 4 2017

\(B=\frac{5}{1.4}+\frac{5}{4.7}+...+\frac{5}{100.103}\)

\(3B=5\left(\frac{1}{1.4}+\frac{1}{4.7}+...+\frac{1}{100.103}\right)\)

\(3B=5\left(1-\frac{1}{103}\right)\)

\(3B=5.\frac{102}{103}\)

\(3B=\frac{510}{103}\)

\(\Rightarrow B=\frac{170}{103}\)

Ta có:

B=\(\frac{5}{1.4}\)+\(\frac{5}{4.7}+.....+\frac{5}{100.103}\)

B=\(\frac{5}{3}\left(\frac{3}{1.4}+\frac{3}{4.7}+....+\frac{3}{100.103}\right)\)

B=\(\frac{5}{3}\left(1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+....+\frac{1}{100}-\frac{1}{103}\right)\)

B=\(\frac{5}{3}\left(1-\frac{1}{103}\right)\)

B=\(\frac{5}{3}.\frac{102}{103}\)

B=\(\frac{170}{103}\)

Vậy B=\(\frac{170}{103}\)

nhớ k

17 tháng 5 2019

\(\frac{3x}{4.7}+\frac{3x}{7.10}+\frac{3x}{10.13}+\frac{3x}{13.16}+...+\frac{3x}{19.22}=\frac{-5}{88}\)

\(\left(\frac{3}{4.7}+\frac{3}{7.10}+\frac{3}{10.13}+\frac{3}{13.16}+...+\frac{3}{19.22}\right)x=\frac{-5}{88}\)

\(\left(\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{10}+\frac{1}{10}-\frac{1}{13}+\frac{1}{13}-\frac{1}{16}+...+\frac{1}{19}-\frac{1}{22}\right)x=\frac{-5}{88}\)

\(\left[\frac{1}{4}+\left(\frac{1}{7}-\frac{1}{7}\right)+\left(\frac{1}{10}-\frac{1}{10}\right)+...+\left(\frac{1}{19}-\frac{1}{19}\right)-\frac{1}{22}\right]x=\frac{-5}{88}\)

\(\left[\frac{1}{4}-\frac{1}{22}\right]x=\frac{-5}{88}\)

\(\frac{9}{44}x=\frac{-5}{88}\)

\(x=\frac{-5}{88}:\frac{9}{44}\)

\(x=\frac{-5}{18}\)

~ Hok tốt ~

17 tháng 5 2019

#)Giải :

Đặt \(A=\frac{3x}{2.7}+\frac{3x}{7.10}+\frac{3x}{10.13}+\frac{3x}{13.16}+...+\frac{3x}{19.22}=-\frac{5}{88}\)

\(A=\frac{3x}{2}+\frac{3x}{7}-\frac{3x}{7}+\frac{3x}{10}-\frac{3x}{10}+\frac{3x}{13}-\frac{3x}{13}+\frac{3x}{16}-...-\frac{3x}{19}+\frac{3x}{22}=-\frac{5}{88}\)

\(A=\frac{3x}{2}+0+0+0+...+0+\frac{3x}{22}=-\frac{5}{88}\)

\(A=\frac{3x}{2}+\frac{3x}{22}=-\frac{5}{88}\)

\(3x:\left(2+22\right)=-\frac{5}{88}\)

\(3x:24=-\frac{5}{88}\)

\(3x=-\frac{5}{88}.24\)

\(3x=-\frac{7}{11}\)

\(x=-\frac{7}{11}:3\)

\(x=-\frac{7}{33}\)

              #~Will~be~Pens~#

28 tháng 3 2017

a,1/1-1/4+1/4-1/7+...+1/2008-1/2011

=(1-1/2011)+(-1/4+1/4)+...+(-1/2008+1/2008)

=1-1/2011+0+...+0

=1-1/2011

=2010/2011

24 tháng 3 2018

a)Ta có: \(\frac{3}{1.4}=\frac{4-1}{1.4}=1-\frac{1}{4}\)

\(\frac{3}{4.7}=\frac{7-4}{4.7}=\frac{1}{4}-\frac{1}{7}\)

... . . . .

\(\frac{3}{n\left(n+3\right)}=\frac{1}{n}-\frac{1}{n+3}\)

\(\Leftrightarrow S=1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{n}-\frac{1}{n+3}< 1^{\left(đpcm\right)}\)

b) Ta có: \(S=\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{9^2}>\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+...+\frac{1}{9.10}\)

   \(\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+...+\frac{1}{9.10}\)

\(=\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{9}-\frac{1}{10}\)

\(=\frac{1}{2}-\frac{1}{10}=\frac{2}{5}\)

Suy ra \(\frac{2}{5}< S\) (1)

Ta lại có: \(S=\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{9^2}< \frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{8.9}\)

Mà \(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{8.9}\)

\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{8}-\frac{1}{9}=1-\frac{1}{9}=\frac{8}{9}\)

Từ đó suy ra S < 8/9

Từ (1) và (2) suy ra đpcm

6 tháng 5 2018

Trả lời

\(B=\frac{5}{1\cdot4}+\frac{5}{4\cdot7}+...+\frac{5}{100\cdot103}\)

\(\frac{3}{5}B=\frac{3}{5}\left(\frac{5}{1\cdot4}+\frac{5}{4\cdot7}+...+\frac{5}{100\cdot103}\right)\)

\(\frac{3}{5}B=\frac{3}{1\cdot4}+\frac{3}{4\cdot7}+\frac{...3}{100\cdot103}\)

\(\frac{3}{5}B=1-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{100}-\frac{1}{103}\)

\(\frac{3}{5}B=1-\frac{1}{103}\)

\(\frac{3}{5}B=\frac{102}{103}\)

\(B=\frac{102}{103}:\frac{3}{5}\)

\(B=\frac{170}{103}\)

6 tháng 5 2018

\(B=\frac{5}{1.4}+\frac{5}{4.7}+...+\frac{5}{100.103}\)

\(B=5\left(\frac{1}{1.4}+\frac{1}{4.7}+...+\frac{1}{100.103}\right)\)

\(3B=15\left(\frac{3}{1.4}+\frac{3}{4.7}+...+\frac{3}{100.103}\right)\)

\(3B=15\left(\frac{1}{1}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+...+\frac{1}{100}-\frac{1}{103}\right)\)

\(3B=15\left(\frac{1}{1}-\frac{1}{100}\right)=15\left(\frac{100}{100}-\frac{1}{100}\right)=15.\frac{99}{100}\)

\(B=\frac{1}{3}.15-\frac{1}{3}.\frac{99}{100}=5-\frac{33}{100}=\frac{500}{100}-\frac{33}{100}=\frac{467}{100}\)

7 tháng 2 2017

a) (\(6\frac{2}{7}.x+\frac{3}{7}\))=-1.\(\frac{11}{5}+\frac{3}{7}\)

(\(6\frac{2}{7}.x+\frac{3}{7}\))=\(\frac{-62}{35}\)

\(\frac{44}{7}.x\)=\(\frac{-62}{35}-\frac{3}{7}\)

\(\frac{44}{7}.x=\frac{-77}{35}\)

x=\(\frac{-77}{35}:\frac{44}{7}\)=\(\frac{539}{1540}\)